Penerapan Model Cooperative Learning TGT untuk Meningkatkan Keaktifan Siswa - Della Bristiana Putri; Dias Raisya Nur Azizah; Fadiyah Halimatus Sa’diyah; M. Makbul; Nur Aini Farida (Universitas Majalengka, 2024)
Lack of student activity in PAI subjects is a problem often found by teachers. The reason for the lack of student learning activity is the use of still conventional learning methods. It requires an interactive teaching model applied by educators to enhance student learning activity. The research is aimed at finding out whether the implementation of the cooperative model type TGT is capable of improving the learning activity of students on the PAI subject in Class IV C SDN Kondangjaya III of 34 students by using Class Action Research as a type of research carried out over 2 cycles. There are four stages of research: planning, implementation, observation, reflection. Researchers collect data through observation sheets, study evaluation tests, field records, and documentation. The results show that the implementation of the cooperative teaching model of the TGT type in PAI subject can improve the learning activity of students of the fourth grade in SDN Kondang Commission III, East Karawang. In the first cycle, the average student data obtained was 71% with the interpretation “Good” and increased the number of 20% to 91% in the second cycle with the “Very Good” interpretation.